2022
DOI: 10.1186/s12888-022-04254-x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempt rate and the risk factors in young, first-episode and drug-naïve Chinese Han patients with major depressive disorder

Abstract: Background: In recent years, the rates of suicide among young people have been increasing, and major depressive disorder (MDD) is regarded to be its main cause. Many factors such as thyroid dysfunction and metabolic abnormalities are thought to mediate this process, but the conclusions are inconsistent. This study investigated the rate of suicide attempts and associated risk factors among young, first-episode and drug-naïve Chinese Han patients with MDD.Methods: A total of 917 patients with MDD (aged 18 ~ 35 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…We noted an independent positive association between the CGI score and suicide attempts in patients with MDD with dyslipidemia of both early-adulthood onset and mid-adulthood onset. Gang Ye's study is consistent with our study showing that CGI is an independent risk factor for suicide attempts in patients with MDD [ 44 ]. The relationship between CGI and suicide attempts may be explained by the following factors: First, the CGI score represents the severity of the disease [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…We noted an independent positive association between the CGI score and suicide attempts in patients with MDD with dyslipidemia of both early-adulthood onset and mid-adulthood onset. Gang Ye's study is consistent with our study showing that CGI is an independent risk factor for suicide attempts in patients with MDD [ 44 ]. The relationship between CGI and suicide attempts may be explained by the following factors: First, the CGI score represents the severity of the disease [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies with large samples of outpatient-treated MDD-diagnosed populations in Shanxi Province, China, also reported almost identical results to ours, and their authors also found that MDD subpopulations with SB with different clinical features had more severe anxiety symptoms, depressive symptoms, psychopathological symptoms, and more severe levels of metabolic parameters [28,21,[29][30][31]. Another report from the MDD population in Anhui, China, also reported similar results to ours [32].…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that serum folate and vitamin B 12 levels were signi cantly and negatively associated with suicide attempts in older patients with depression, whereas serum ferritin levels were not signi cantly associated with suicide attempts. Previous studies 30 found a positive association between low cholesterol levels and suicide attempts in patients with depression. However, no study con rmed whether there was an association between ferritin, folate, and vitamin B 12 and suicide attempts in older depressed patients.…”
mentioning
confidence: 79%